Undergraduate students’ perceptions of a career in hospitality industry / Nurul Hidayah Norkhamar and Nur Laila Abdul Latip - Norkhamar, Nurul Hidayah; Abdul Latip, Nur Laila (Faculty of Hotel and Tourism, Universiti Teknologi MARA, 2017)
The aim of this study is to investigate undergraduate’s student perception about career in hospitality industry. The research design used was the quantitative research design and research questionnaire was the main research instrument for this study. Questionnaire used in this study was an online questionnaire. To achieve the objectives, the respondents had selected convenient from the undergraduate students from UITM Dungun, Terengganu. A total of 160 respondents participated in this study. The respondents had completed a questionnaire regarding factor that influencing their career choice in hospitality industry (14 items) and their perception of a career in hospitality industry (6 items). The finding was analysed by using Statistical Program for the Social Science software (SPSS). The result presented descriptive analyses based on the factors and respondents' perception o f a career in the hospitality industry. Overall, there are positive and negative perceptions of career in hospitality industry among the undergraduate students in Terengganu. Besides that, factors that influence career choice of undergraduate students in hospitality industry are nature of work, social status and physical working condition.